Edukasi Cara Mengolah Data Geoteknik Tambang Bagi Pelajar di SMKN 4 Kota Palangka Raya - Yossa Yonathan Hutajulu; Nuansa Mare Apui Ganang; Yunida Iashania; I Dewa Made Prawindya Kumara (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Data processing is one of the steps that must be done well before you can draw good and correct conclusions. Often the data obtained cannot be utilized as well as possible due to a lack of knowledge regarding its use and how to process it. This activity includes an introduction to software, division of data types, use of each data and how to process geotechnical data so that further analysis can be carried out. Assessment of each instrument regarding slope stability and underground opening hole stability needs to be given as early as possible to prepare students to improve their abilities and have adequate knowledge. This increase in skills and knowledge will increase the value of graduating students at SMK Negeri 4 Palangka Raya in particular.